Virtualization technology in teaching information technology security - Masud, Mohd Zaki; Hamid, Erman; Mat Ariff, Nor Azman; Abdollah, Mohd Faizal; Selamat, Siti Rahayu (2010)
The effective way to educate students on using technologies is through hands-on experience. Learning a subject by hands-on experience can synchronize their head and hands, making the subject matter easier to be absorbed as well as stimulating the mind of the students to be more creative and innovative. In teaching information Technology Security, exposing the student to real-time scenario of threat and safeguarding network resources expose the student to the real danger of exploitation and the devastating effect of security breach on network infrastructure. Unfortunately this requires a huge amount of time and cost for preparing and setting up the equipment and software for the practical session. Moreover, most of the activity in a security subject can also jeopardize other devices in the real network, for instance simulating a worm attack or hijacking server attack might affect the whole network of the campus. Thus, a special laboratory environment that can be set up with minimal cost, is easy to manage and can isolate the hazardous activities from the real environment is needed. In order to alleviate this problem, this paper presents an implementation of Virtualization Technology in teaching Information Technology Security which allows labs to progress in a secure and portable manner while providing additional protection for the real systems.